2015
DOI: 10.3390/molecules201219780
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment and Purification of Polyphenol Extract from Sphallerocarpus gracilis Stems and Leaves and in Vitro Evaluation of DNA Damage-Protective Activity and Inhibitory Effects of α-Amylase and α-Glucosidase

Abstract: An efficient preparative separation method for Sphallerocarpus gracilis stems and leaves polyphenols (SGslP) was established in this study. An X-5 macroporous adsorption resin was selected for the purification of the SGslP, and the polyphenol content of the purified SGslP (PSGslP) was increased 5.11-fold from 8.29% to 42.38% after one treatment run. The chemical composition of the PSGslP was analyzed by HPLC-MS/MS, and the predominant compounds were found to be luteolin-7-glucoside, acacetin-7-acetyglycoside a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
4
6
1
Order By: Relevance
“…Acarbose, a α-glucosidase inhibitor, was used as positive control in many types of research to evaluate the inhibitory effect of bioactive compounds on α-glucosidase. [3,30] Surprisingly, in the present study, the IC 50 values of the inhibitory effects of the phenolic extracts were even significant lower than that of the acarbose. Additionally, the inhibitory activities on α-glucosidase found in this study were markedly higher than those of reported for other beans.…”
Section: Inhibitory Effects On α-Glucosidase and Lipase At Different contrasting
confidence: 83%
See 1 more Smart Citation
“…Acarbose, a α-glucosidase inhibitor, was used as positive control in many types of research to evaluate the inhibitory effect of bioactive compounds on α-glucosidase. [3,30] Surprisingly, in the present study, the IC 50 values of the inhibitory effects of the phenolic extracts were even significant lower than that of the acarbose. Additionally, the inhibitory activities on α-glucosidase found in this study were markedly higher than those of reported for other beans.…”
Section: Inhibitory Effects On α-Glucosidase and Lipase At Different contrasting
confidence: 83%
“…The α-glucosidase inhibitory activity was measured as described by Ma et al [30] with slight modifications. Briefly, 0.1 mL of pehnolic solutions or acarbose solutions with different concentrations were added to 0.1 mL of 1.25 U/mL α-glucosidase solution.…”
Section: Enzyme Inhibition Assay α-Glucosidase Inhibition Assaymentioning
confidence: 99%
“…Foods, especially fruits rich in polyphenols, offer an attractive means of managing postprandial hyperglycemia for type 2 diabetes by controlling starch breakdown and intestinal glucose absorption (30, 39). Thus, the inhibitory effects of α-amylase and α-glucosidase in kiwifruit and kiwifruit products during in vitro GI digestion were investigated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The methods used for the α-amylase enzymatic inhibition assays performed in this study were adapted from those developed in a previous study (30), with slight modifications. In addition, the α-glucosidase inhibitory activity was measured as described in a previous report (30), with slight modifications. The inhibitory activity (I) was calculated using the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…where IA is the percent of -amylase inhibition, C is the concentration of starch in the control reaction, and S is the concentration of starch in the test sample [34][35][36]. Differences between groups were considered to be significant at < 0.05.…”
Section: Evaluation Of Alg Influence On Mf Hypoglycemic Activitymentioning
confidence: 99%